Is the Bible God's Word? Jimmy Swaggart : Deedat's American tour - Sweggart, Jimmy; Deedat's American tour (Durban, South Africa : Islamic Propagation Center International ; Elgin, Ill. : Community Production [n.d.])
Present a debate of Muslim and Christian theory'proof' between christian fundamentalist Jimmy and muslim scholar Ahmed Deenat
Keywords: Bible -- Critism, interpretation, etc; Bible -- Islamic interpretations